ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPUASAN KERJA TENAGA MEDIS DI PUSKESMAS KOTA PADANG - Winanda, Winanda; Nindrea, Ricvan Dana (Jurnal Endurance, 2017)
The number of medical personnel in the Padang City is still a shortage of the amount required is 83 people, but this time medical personnel numbered 53 people. This research was carried out by combining two types of research are mixed method, preceded by a quantitative research with cross sectional approach, followed by qualitative research. The study was conducted in Primary Health Care Padang City. The population in this study are all medical personnel in the Padang City with a sample of 38 people, with a sampling technique is simple random sampling. The bivariate analysis known there are significant relationship between work (p = 0,023), compensation (p = 0,001), supervision (p = 0,001) and the relationship between employees (p = 0,000) with job satisfaction. But there is no relationship promotion with job satisfaction (p = 0,208). The conclusion of the study there are significant relationship between work, compensation, supervision and the relationship between employees with job satisfaction.